Plasmachemical synthesis and evaluation of the thermal conductivity of metal-oxide compounds for prospective nuclear fuel; Journal of Physics: Conference Series; Vol. 1145 : Prospects of Fundamental Sciences Development (PFSD-2018) - Shamanin I. V. Igor Vladimirovich; Karengin A. G. Aleksandr Grigorievich; Novoselov I. Yu. Ivan Yurievich; Karengin A. A. Alexey Alexandrovich; Alyukov E.; Poberezhnikov A. D. Andrey Dmitrievich; Babaev R.; Mendoza O. (2019, 2019)
Title screen